THE EFFECTIVENESS OF MYOFASCIAL RELEASE IN THE CERVICAL REGION FOR TENSION HEADACHE RELIEF - Paula Nunes Christofoletti, Ana (Health and Society, 2021)
Myofascial release is a manual thrust applied to the body face to treat the facial system. Myofascial release restores the flexibility and elasticity of the fascia, thus having a broad ability to alter the body's range of motion and dissolve restrictions in the fascial tissues. Sedentary lifestyle and positions that cause pain can gradually cause muscle and fascial restrictions and shortening. This study aims to identify the effectiveness of myofascial release in the cervical region for tension headache relief. This study is characterized as a bibliographical research of qualitative descriptive character, where the researcher is the one who describes the research object, assuming the role of observer and explorer, directly collecting the data in the place where the study phenomena occurred or appeared. It is concluded that through the use of this technique, it is possible to deactivate trigger points, promote a correct alignment of the body structure, minimize movement restriction and pain without compromising the myofascial structures.